The Preacher and the Critic - Lillie, William (Scottish journal of theology, 1953)
Dr R. E. McIntyre in his recent Warrack lectures tells of a minister, who made the boast, ‘I am an evangelist, thank God, and not a theologian’. The writer of this article can make a similar claim without the thanksgiving, ‘I am a preacher, and not a Biblical critic’. The learned men of Biblical Criticism have, however, set for us preachers a problem in Christian ethics. The findings of Biblical Criticism being what they are, can we go on preaching in the way that we have been doing? Most of us in our preaching imply, if we do not explicitly state, that the words attributed to our Lord in the New Testament are translations of words that Jesus actually uttered during His life on earth. Indeed, we try to bring out every possible meaning of these words in the light both of the circumstances in which they are said to have been uttered and in the light of the whole religious heritage of the Jews which Jesus shared. There is a similar problem in preaching from any part of Scripture, but, in this article, I shall confine myself for the most part to sayings attributed to our Lord Himself. One reason for doing so is the very practical one that I have found a rich mine of examples in Dr T. W. Manson's recently reprinted work, The Sayings of Jesus; another reason is that whatever we discover to be right method in the case of the sayings attributed to our Lord is likely, with necessary changes, to be right method in the case of the rest of the Scripture records.